Peluang Penelitian Sosiologi Wisata Makanan: Sebuah Analisis Bibliometrik: Sociology of Food Tourism Research Opportunities: A Bibliometric Analysis - Agustina Multi Purnomo (Society, 2022)
This research aims to formulate sociological research opportunities in food tourism. The study used the literature review method with bibliometric analysis to find the most discussed issues and opportunities for discussing new problems that have yet to be widely discussed. This research used VOSViewer software edition 1.6.18 to analyze 3,055 research articles on the ScienceDirect website from 1999-2023. The publication period is divided into three according to the ability to download, which can only download 1000 articles in each period. This research analyzed the development of publications, publishers, scope, main keywords, clusters, density visualization maps, overlays, and research networks. The analysis found that the research on the sociology of food tourism has increased, but sociology journals have yet to become publishers with the highest number of articles. Research opportunities exist on the topics of policy, inequality, and migration. Opportunities also exist in relating new and old issues to other matters. Previous studies have yet to study many interactions between actors providing food and other actors forming food tourism destinations. It is suggested that further research covers the topics of policy, inequality, migration, sociological theorizing of food tourism, and interactions between actors in the production of tourist attractions.